Zip Zap Wickety Wack : a story about sharing - Diffee, Matthew (New York : Neal Porter Books / Holiday House, 2025)
"Farm animals share their sounds, but humorous drama ensues when the goat and the sheep both lay claim to "baa.""--.
kids book 2025 fall.
Ages 4-8.
Grades K-1.
Keywords: Domestic animals -- Fiction; Animal sounds -- Fiction; Sharing -- Fiction; Animal fiction; Picture books; Humorous fiction